EMPLOYEE RETENTION STRATEGIES IN A - Lorenzo, Claudio (My University, 2011)
For many engineering organisations, key skill retention, employee engagement and employee motivation form the basis of their strategy to remain competitive in the long run. In essence what these organisations strive for is to achieve a high level of organisational commitment. Under the current surge of engineering activities the global demand for qualified engineers has increased sharply and engineering organisations are increasingly facing problems in motivating and retaining their employees. This research has provided valuable understanding on how a global engineering company view the potential benefits of a long-term relationship with its employees and what structures are in place in order to create an environment where skills are retained within the organisation. The findings of this research indicated that employee turnover has a negative effect on a global engineering organisation mainly due to the loss of knowledge, training costs and the perceptions of instability it creates in the market place. The research also indicated that the employee turnover can impact positively on the running of the business as it allows for the inflow of employees with new ideas, experiences and specific skills and abilities The research has confirmed that the employees of an engineering organisation have specific characteristics and needs. These findings are then integrated into a model which highlights how a global engineering organisation deals with the knowledge worker’s needs through its retention strategies.
MBA - WBS
Keywords: Retention of employees; Employees, Retention of; Engineering firms